2015
DOI: 10.1007/s11356-015-5493-4
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effect of zinc oxide and titanium oxide nanoparticles on growth and chlorophyll a content of Picochlorum sp.

Abstract: The use of nanoparticles (NPs) is of increasing significance due to their large potential for various applications. Great attention should be paid on the possible impacts of nanoparticles on the environment as large amounts of them may reach the environment by accident or voluntarily. Marine algae are potential organisms for usage in nanopollution bioremediation in aquatic system, because of their ability to adapt to long exposure to NPs. Thus, it is of prime importance to study the possible interactions of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 66 publications
(96 reference statements)
3
31
0
Order By: Relevance
“…Negative effect of TiO 2 NPs on chlorophyll a concentration during the early growth stages of algae (Picochlorum sp.) has been also reported (Hazeem et al, 2016). However, there are other diverse reports showing TiO 2 NPs have no effect on chlorophyll and carotenoid content in bread wheat (Larue et al, 2012) and even promoted chlorophyll formation in spinach and mung bean (Raliya et al, 2015).…”
Section: Foliar Application Of Tio 2 Nps Under Normal Irrigationmentioning
confidence: 90%
“…Negative effect of TiO 2 NPs on chlorophyll a concentration during the early growth stages of algae (Picochlorum sp.) has been also reported (Hazeem et al, 2016). However, there are other diverse reports showing TiO 2 NPs have no effect on chlorophyll and carotenoid content in bread wheat (Larue et al, 2012) and even promoted chlorophyll formation in spinach and mung bean (Raliya et al, 2015).…”
Section: Foliar Application Of Tio 2 Nps Under Normal Irrigationmentioning
confidence: 90%
“…Nanotechnology offers a great advantage in the field of chemical priming as the effectiveness of chemicals can be enhanced in their nano-form, thus reducing their environmental load (Khan et al, 2017). A wide range of nanoparticles (NPs), such as zinc oxide (nZnO), titanium oxide (nTiO 2 ), cerium dioxide (nCeO 2 ), silicon dioxide (nSiO 2 ), magnetite (nFe 3 O 4 ), aluminium oxide (nAl 2 O 3 ), copper oxide (nCuO) and carbon nanotubes, have been tested for their potential towards growth promotion and stress amelioration in plants (Marchiol et al, 2016;Abdel Latef et al, 2017), diatoms (Deng et al, 2016) and algae (Hazeem et al, 2016). nTiO 2 is one of the major engineered NPs produced in large quantities by cosmetics, chemical, agriculture and food industries (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to our results, seed priming may be an effective method to enhance the growth parameters. Seed priming with ZnO NPs has been reported by Munir et al (2016) As concern to nanoparticle dose, Hazeem et al (2016) reported lower Zn concentration in cucumber shoot with Zn NPs concentration of 125 mg/kg than 25 mg/kg which could be due to higher Zn levels that deform the plant cells. While, contrary to this, Moghaddasi et al (2017) reported higher Zn concentrations in plants treated with high NPs concentration and correlated it with higher penetration of NPs into plant cells However, more studies are required to understand the absorption mechanism within the plant cells.…”
Section: Effect Of Zno Nps On Growth Biomarkersmentioning
confidence: 88%